Response of Six Turfgrass Species and Four Weeds to Three HPPD‐Inhibiting Herbicides. (1st July 2017) - Brewer, John R.; Willis, John; Rana, Sandeep S.; Askew, Shawn D.
Abstract : Core Ideas: Tembotrione controlled weeds selectively in bluegrass, fescue, and zoysiagrass turf. Topramezone controlled key weeds better than mesotrione and tembotrione. Topramezone was among the safest herbicides on four of the six turfgrasses tested. Results will aid herbicidal‐risk assessment near potentially sensitive turfgrass species. The study supports considerations for herbicide label expansion or registration in turf. Mesotrione (2‐[4‐(methylsulfonyl)‐2‐nitrobenzoyl]‐1, 3‐cyclohexanedione), tembotrione (2‐[2‐chloro‐4‐(methylsulfonyl)‐3‐[(2, 2, 2‐trifluoroethoxy)methyl]benzoyl]‐1, 3‐cyclohexanedione), and topramezone ([3‐(4, 5‐dihydro‐3‐isoxazolyl)‐2‐methyl‐4‐(methylsulfonyl)phenyl](5‐hydroxy‐1‐methyl‐1 H ‐pyrazol‐4‐yl)methanone) are new herbicides that control many troublesome weeds, but little is known about the response of several turfgrass species to these herbicides. A multiyear study was conducted to determine the response of six turfgrass species and four weeds to these three herbicides. Study results generally agreed with previous reports of turfgrass and weed response to mesotrione, and suggest that tembotrione could be safely used, depending on rate, to control weeds such as smooth crabgrass [ Digitaria ischemum (Schreb.) Schreb. ex Muhl.], broadleaf plantain ( Plantago major L.), and white clover ( Trifolium repens L.) selectively in tall fescue [ Schedonorus arundinaceus (Schreb.) Dumort., nom. cons.], Kentucky bluegrass ( Poa pratensis L.), and zoysiagrass ( Zoysia japonica Steud.) turf. Topramezone at 36.8 g a.i. ha −1 controlled smooth crabgrass and white clover better than mesotrione or tembotrione, and smooth crabgrass control by topramezone had similar results as in other studies. Predicted maximum turfgrass injury based on the Gaussian function applied over time generally showed that maximum injury caused by topramezone was less than tembotrione and mesotrione on creeping bentgrass ( Agrostis stolonifera L.) and perennial ryegrass ( Lolium perenne L.), less than tembotrione and equivalent to mesotrione on tall fescue and perennial ryegrass, equivalent to tembotrione and more than mesotrione on bermudagrass [ Cynodon dactylon (L.) Pers.], and more than tembotrione and mesotrione on zoysiagrass. The area under the progress curve per day of visual injury and normalized difference vegetation index were consistent with trends in predicted maximum injury.